If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 + -8 = 0 Reorder the terms: 8 + -8 + 3x = 0 Combine like terms: 8 + -8 = 0 0 + 3x = 0 3x = 0 Solving 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 0 Simplifying x = 0
| -5(v-3)=6 | | 5z+6=26 | | 10x+11x=126 | | 5x+6x-8x-20=4 | | -16x^2-108x+160=0 | | 11x+y=180 | | 3y+11+7x+4=180 | | f(x)=x^3-3x^2-9x+4 | | 20+7y=-6+15y | | (3x-14)+2x+25=180 | | (x-(2+2i))(x-(2-2i))(x+1)(x-2)= | | 26=-2y | | 8-5n=-2 | | 5x+6x-8x=24 | | 5.75x+3.5=9.25x | | (5x+9)(8x-15)=180 | | 4(w-5)=3(w+3) | | y=x^2+14x-32 | | 6+7(n-7)=-85 | | 4z+5=6z+10 | | 3=-2(x+2) | | 7(4n+5)=5(2n+7) | | y(y-3)+6=2y | | G-9.3=9.2 | | 4y-2y+18=12 | | 5n-8n+4= | | 6+7n-49=-85 | | 20m+12=30m-18 | | -2p+6-8p+9= | | 9-5c=12-(6c-7) | | 9(x-3)=63 | | 4+6x-4=3x |